2020
DOI: 10.1116/6.0000047
|View full text |Cite
|
Sign up to set email alerts
|

Plasma enabled devices for the selective capture and photodynamic identification of prostate cancer cells

Abstract: Prostate cancer is the second most common cancer in men and the second leading cause of male cancer deaths. The current blood test for detecting prostate cancers measures prostate-specific antigen. It has many limitations including a very high rate of false positives. Herein, prostate-specific membrane antigen (PSMA) based immunocapture and hexaminolevulinate (HAL) based photodetection are integrated into a new diagnostic device designed to selectively identify whole prostate cancer cells from voided urine wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Figure 3c shows a representative micrograph of AuNPs bound to PiPOx films deposited at 20 W, 0.12 mbar for 240 s. The individual nanoparticles are randomly distributed without aggregates, which indicates that the particles are bound to the surface strongly enough not to be disrupted by capillary forces during the drying step, which is in good agreement with previous reports which have established the covalent nature of the bond between POx film and AuNPs. [ 19 ] The reactivity of the POx films towards biomolecules was confirmed via ToF SIMS using anti‐prostate specific membrane antigen (PSMA) and skim milk blocking proteins. Fragments corresponding to amino acid (i.e., C 4 H 8 N + attributed to proline, C 4 H 10 N + valine, C 5 H 10 N + for lysine, and C 5 H 12 N + for leucine) were detected post biofunctionalization on both MePOx and PiPOx, as discussed in detail in Figure S9, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3c shows a representative micrograph of AuNPs bound to PiPOx films deposited at 20 W, 0.12 mbar for 240 s. The individual nanoparticles are randomly distributed without aggregates, which indicates that the particles are bound to the surface strongly enough not to be disrupted by capillary forces during the drying step, which is in good agreement with previous reports which have established the covalent nature of the bond between POx film and AuNPs. [ 19 ] The reactivity of the POx films towards biomolecules was confirmed via ToF SIMS using anti‐prostate specific membrane antigen (PSMA) and skim milk blocking proteins. Fragments corresponding to amino acid (i.e., C 4 H 8 N + attributed to proline, C 4 H 10 N + valine, C 5 H 10 N + for lysine, and C 5 H 12 N + for leucine) were detected post biofunctionalization on both MePOx and PiPOx, as discussed in detail in Figure S9, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…In previous works, we showed that immunofunctionalised POx films deposited for four or five minutes do successfully and specifically capture prostate cancer cells (which overexpress PSMA), but not healthy prostate cells. [ 19,20 ] Here we tested significantly thinner MePOx and PiPOx deposited for only 30 and 50 s. A 1:1 mixture of healthy PNT2 cells and cancerous LNCaP cells was introduced into the channel and left to react with the immunofunctionalized POx surface for 45 min before rinsing with PBS. Figure 3e shows representative images of the number of healthy (blue dapi stain) and cancer cells (Nuclear red stain) present in the microchannel before and after rinse.…”
Section: Resultsmentioning
confidence: 99%
“…Then, 1 mg mL −1 skim milk solution, acting as a block solution, was added to both the test and the negative control channels for 45 min. The slides were rinsed with phosphate-buffered saline (PBS) three times, and fresh PBS was added afterward [ 21 ]. Following this procedure, the PPOx coating present in the negative control channel is blocked by the skim milk proteins, which prevents the non-specific binding of any cell types.…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported on the development of a microfluidic device capable of capturing PCa cancer cells spiked in healthy urine [ 21 ]. In these original works, the PCa cells were specifically captured from cell populations comprising both cancer and healthy cells spiked at a 1:1 ratio.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, PPOx coatings have been used in commercial microfluidic chips for selective isolation of both bladder and prostate cancer cells from urine samples (Macgregor-Ramiasa et al, 2017;Hanieh Safizadeh Shirazi, 2020;Macgregor et al, 2021). These urothelial cancers readily shed cancer cells in urine, so detecting these cancer cells from urine samples could become an alternative to the current invasive diagnostic methods which consist of cystoscopy and/or biopsy (Chan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%